The Effects of Acute Transcranial Direct Current Stimulation on Attentional Bias in Pedophilic Disorder: A Preregistered Pilot Study. Issue 5 (1st October 2020) - Pezzoli, Patrizia; Ziogas, Anastasios; Seto, Michael C.; Jaworska, Natalia; Mokros, Andreas; Fedoroff, Paul; Santtila, Pekka
Abstract: Objectives: Individuals with pedophilic disorder (PD) experience personal and interpersonal difficulties and are at risk of sexually offending against children. As such, innovative and empirically validated treatments are needed. Recent studies have indicated that men who have sexually offended against children (SOC) with PD display an automatic attention bias for child‐related stimuli as well as reduced activity in the dorsolateral prefrontal cortex (dlPFC), a brain area involved in cognitive control, including control over sexual arousal. In this preregistered pilot study, we are the first to investigate whether acutely increasing prefrontal activity could reduce the putative pedophilic attention bias. Materials and Methods: We delivered a single 20‐min session of active anodal versus sham transcranial direct current stimulation (tDCS) over the left dlPFC to 16 SOC with PD and 16 matched healthy controls, while they performed a task requiring controlled attention to computer‐generated images of clothed and nude children and adults. We collected responses unobtrusively by recording eye movements. Results: Our results did not support the presence of the expected automatic attention bias across outcome measures. Nonetheless, we found a response facilitation with child targets in patients and, unexpectedly, in controls, likely due to unwanted salience effects. Active versus sham tDCS reduced this bias across groups, as indicated by a significant group*condition interaction ( p = 0.04). However, no attentional bias and no tDCS effects on attentional responses to child and adult images emerged following tDCS. Conclusions: These results suggest enhanced cognitive control in response to salient stimuli during active tDCS. Thus, to assist future studies on neuromodulation in PD, we provide suggestions for design improvement.